2022
DOI: 10.3390/ani12091053
|View full text |Cite
|
Sign up to set email alerts
|

Returning a Shelter Dog: The Role of Owner Expectations and Dog Behavior

Abstract: Millions of animals are adopted from animal shelters in the United States each year, although some are returned post-adoption, which can decrease both the animals’ chances of future adoptions and the owners’ willingness to adopt again. In this study, we investigated the impact of adopter expectations for ownership and animal behavioral problems on post-adoptive dog returns at a large animal shelter in South Carolina. Between June–September 2021, 132 dog adopters completed a survey about their expectations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 42 publications
0
23
1
Order By: Relevance
“…Not all adoptions are successful and managing owner expectations preadoption is difficult to navigate. If owner expectations are high and skewed based on limited knowledge, they may be difficult to achieve and therefore returns are more likely [ 12 ]. Well respected scientists have attempted to understand this phenomenon and investigate underlying motivating factors influencing long term success in pet dog adoptions.…”
Section: Introductionmentioning
confidence: 99%
“…Not all adoptions are successful and managing owner expectations preadoption is difficult to navigate. If owner expectations are high and skewed based on limited knowledge, they may be difficult to achieve and therefore returns are more likely [ 12 ]. Well respected scientists have attempted to understand this phenomenon and investigate underlying motivating factors influencing long term success in pet dog adoptions.…”
Section: Introductionmentioning
confidence: 99%
“…A further key factor to achieve a conscious choice is based on the expectations of the adopters towards dog ownership, prior to adoption itself and their gained experience with dog behavior. Powell and coworkers documented that owners who returned their dog to the shelter within three months from the adoption had higher expectations of their dog and human–dog relationship, although animals exhibited a non-dysfunctional behavior when compared with adopters who did not return their dogs [ 37 ]. The same authors found that two-thirds of owners experienced dog behavioral concerns following adoption, even though some of them reduced over time (e.g., difficulties with training and fear).…”
Section: Discussionmentioning
confidence: 99%
“…In looking across reported findings on age, there is agreement and contradiction, driven partly by differences in scope and methodology, and potentially by location and culture. Powell et al [ 54 ] in a study on returns found that dogs older than 6 months, and medium to large size, at adoption, were more likely to be returned. Cain et al [ 29 ] found that when comparing senior to adult dogs, senior dogs had a lower chance of adoption as the length of stay increased until the 50-day mark, when senior dogs were more likely to be adopted than adult dogs.…”
Section: Discussionmentioning
confidence: 99%